PSYCHOLOGICAL READINESS OF INTERNALLY DISPLACED WOMEN FOR MOTHERHOOD AS A PSYCHOLOGICAL PHENOMENON (Psychology Travelogs, 2024)
The article is devoted to the study of psychological readiness for motherhood in women who are internally displaced persons as a multidimensional psychological phenomenon. Psychological readiness for motherhood involves the integration of cognitive, emotional, motivational, and behavioral components that are formed under the influence of external and internal factors. In the case of internally displaced women, these components are significantly affected by the conditions of forced displacement, which are accompanied by psychological stress, social isolation, financial instability, and losses.Special attention is given to the impact of war and displacement on women's emotional state, their perceptions of motherhood, and their ability to adapt to new social and living conditions. It is noted that women who experience the loss of home, social support and a stable environment often face high levels of anxiety, depression and a decreased sense of security, which directly affects their readiness for the maternal role.The peculiarities of the formation of psychological readiness for motherhood in the conditions of constant stress caused by war are revealed. The key aspects contributing to the formation of a positive attitude to motherhood are identified, in particular, individual resources of women, availability of social support, access to psychological assistance and information training. It is found that women who receive emotional and social support show a higher level of readiness for motherhood, despite difficult living conditions.The practical significance of the work lies in the proposal of psychological support programs for internally displaced women who are planning to become mothers or are already in the process of becoming mothers. It is recommended that such programs include elements of psychoeducation, emotional calming techniques, group therapy and individual counseling. This will help to stabilize the emotional state, increase self-esteem and recognize the importance of the maternal role.The study highlights the need for a comprehensive approach to the study of IDPs' psychological readiness for motherhood, taking into account their individual and socio-cultural characteristics. This will contribute to understanding the specificities of adjustment in the context of forced displacement and help to develop effective strategies for psychological support.
Keywords: psychological preparedness; motherhood; internally displaced; war; adapting